2018
DOI: 10.1101/411165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New genetic variants associated with major adverse cardiovascular events in patients with acute coronary syndromes and treated with clopidogrel and aspirin

Abstract: Importance:Although a few studies have reported the effects of several polymorphisms on major adverse cardiovascular events (MACE) in patients with acute coronary syndromes (ACS) and those undergoing percutaneous coronary intervention (PCI), these genotypes account for only a small fraction of the variation and evidence is insufficient. This study aims to identify new genetic variants associated with MACE by large-scale sequencing data. Objective: To identify the genetic variants that caused MACE. Design: All … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In fact, c.489G > A (p.Pro163=) (rs140410716) has been revealed as a disease modifier itself and has been associated with worse cardiac outcomes in a genome study of Han Chinese patients who had undergone STENT for acute coronary syndromes. Additionally, the study found lowered ECHS1 expression to be associated with a more severe clinical phenotype (Liu et al, 2018). Another study interested in genomic modifiers of coronary disease found a clear correlation of drug refractory dilated cardiomyopathy and several polymorphisms in ECHS1 (Campbell et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…In fact, c.489G > A (p.Pro163=) (rs140410716) has been revealed as a disease modifier itself and has been associated with worse cardiac outcomes in a genome study of Han Chinese patients who had undergone STENT for acute coronary syndromes. Additionally, the study found lowered ECHS1 expression to be associated with a more severe clinical phenotype (Liu et al, 2018). Another study interested in genomic modifiers of coronary disease found a clear correlation of drug refractory dilated cardiomyopathy and several polymorphisms in ECHS1 (Campbell et al, 2018).…”
Section: Discussionmentioning
confidence: 92%